Tingkat Efektivitas Sistem Peringatan Dini Banjir di Sepanjang Sungai Ciliwung (Studi Kasus: Kebon Baru, Kampung Melayu, Bukit Duri, dan Bidara Cina - Kevin Thrustinadi Wibowo Wuri; Parfi Khadiyanta (Teknik PWK (Perencanaan Wilayah Kota), 2018)
The Ciliwung River is one of the rivers that routinely causing flood in its area, which has an impact on property and life losses. But in order to reduce the impact caused, the government cooperated with several other parties to take precautionary and preparedness measures, one of which was the existence of an early warning system. The effectiveness of the flood early warning system in the Ciliwung River was assessed using four variables, namely knowledge about flood risk, monitoring and flood early warning services, dissemination and communication of flood early warning systems, and the ability to respond. The assessment of the effectiveness of the early warning system was carried out in four villages, Kebon Baru, Kampung Melayu, Bidara Cina, and Bukit Duri, which represented an early warning system on the Ciliwung River. Scoring results found that the flood early warning system in the Ciliwung River was effective because the average scoring of each question was 2 and 3 which indicated that the existing early warning went well with the support of the government, the community, other parties and the support of equipment and good technology.